ROKOK, KEBIASAAN MEROKOK DAN ANGKA KEMISKINAN DI PULAU JAWA - Setiyani, Mei Handriati; Kristiyanto, Sony (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Poverty is a major problem faced by all countries, including Indonesia. Several studies have shown that the problem of poverty is influenced by several factors, both economic and non-economic factors. This study intends to look more deeply and comprehensively from different perspectives on poverty in Indonesia, especially poverty in Java. It is estimated that smoking behavior and habits in Indonesia can affect poverty rates because generally, cigarette consumers are dominated by people with lower welfare levels. Furthermore, it is also known that the percentage of spending on cigarette consumption is actually higher when compared to the percentage for education or health. The focus of this research is regencies and cities in Java Island in 2021. This research comes to the conclusion that smoking behavior has a positive and significant effect, while other variables, namely TPAK and Gross Domestic Product Regional rates can also influence poverty rates on Java Island.